2018
DOI: 10.1016/j.compscitech.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying fibre reorientation during axial compression of a composite through time-lapse X-ray imaging and individual fibre tracking

Abstract: The sudden compressive failure of unidirectional (UD) fibre reinforced composites at loads well below their tensile strengths is a cause of practical concern. In this respect and more generally, analytical and numerical models that describe composite behaviour have been hard to verify due to a lack of experimental observation, particularly in 3D. The aim of this paper is to combine fast in-situ X-ray computed tomography (CT) with advanced image analysis to capture the changes in fibre orientation in 3D during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…The kink-plane angle has been characterised post-mortem and not in-situ. However, recent results from notched circular specimens show that the kink-plane orientation is very similar from initiation to final failure [4], supporting the validity of the post-mortem analysis performed here.…”
Section: Experimental Compression Testssupporting
confidence: 87%
See 2 more Smart Citations
“…The kink-plane angle has been characterised post-mortem and not in-situ. However, recent results from notched circular specimens show that the kink-plane orientation is very similar from initiation to final failure [4], supporting the validity of the post-mortem analysis performed here.…”
Section: Experimental Compression Testssupporting
confidence: 87%
“…Geometric information of the kink-bands was obtained and information about the failure mechanisms within the kink-band was provided from tomographic reconstructions with high spatial resolution. CT monitored compressive tests have also been performed to study damage growth in-situ [3,4]. The progression of a kink-band can occur with very high speed and an attempt to capture this using ultra-fast time-laps CT with a synchrotron X-ray source was made by Ueda et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no results are presented on in situ following the damage accumulation. Emerson et al ([31]), have reached a fibre-by-fibre detection level, characterising orientation in glass and carbon fibre composites from relatively low contrast images, and presented quantitative results on the axial compression of composites in [32]. Where Emerson's algorithm comprises a training process to generate a dictionary that reduces the degree of false centre detection, in this study a simple Otsu's threshold ( [33]) has been shown to track fibres accurately.…”
Section: Introductionmentioning
confidence: 93%
“…piezoelectric transducer-based (19,20) and angle beam transducer-based (21,22) ), air-coupled ultrasonics (23)(24)(25)(26)(27)(28)(29)(30) , thermography (31)(32)(33)(34)(35)(36) , optical fibre sensing (37)(38)(39)(40)(41)(42) , digital image correlation (DIC) (43)(44)(45)(46)(47)(48) , electromagnetic testing (49)(50)(51) (e.g. eddy current (52)(53)(54)(55)(56)(57)(58) ) and X-ray imaging (59,60) . In particular, acoustic emission sensors are used to detect bursts of acoustic waves from the fracture events (e.g.…”
Section: Introductionmentioning
confidence: 99%